ISSUES OF TOLERANCE, NATIONAL IDENTITY AND IDEOLOGICAL IMMUNITY ARE BECOMING INCREASINGLY RELEVANT IN THE PROCESS OF GLOBALIZATION - Iqboloy Ghairatovna, Faizullayeva (Journal of Higher Education and Academic Advancement, 2024)
Objective: With an emphasis on the difficulties and solutions for maintaining cultural values in the face of global integration, this study attempts to investigate how globalization has affected Uzbekistan's national identity, tolerance, and ideological immunity. Method: The impact of globalization on Uzbekistan's social and cultural structures was evaluated through a qualitative analysis that combined historical, sociological, and ideological frameworks. Policy documents, cultural studies, and interviews with important players in the preservation of national identity were the sources of the data. Results: The report highlights the main dangers of globalization, such as the loss of national identity and cultural uniformity. Along with outlining strategies for maintaining ideological immunity, it highlights how national policies and neighborhood projects can foster cultural resilience. A number of adaptation techniques are put forth to preserve cultural values and provide stability in the face of external forces. Novelty: By providing fresh perspectives on the idea of intellectual immunity as a safeguard against cultural dilution in a globalized environment, this study adds to the scant literature on the relationship between globalization and national identity in Central Asia.